Regarding setting alkali resistant mesh cloth in CM6 finishing project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the set up of alkali resistant mesh cloth in CM6 finishing work of BRACU new campus project.